Méliès - Méliès, Georges ([Paris] : Arte Video, 2008)
Méliès le cinémagicien: This film recreates the life and work of Georges Méliès, who created over 500 silent films between 1898 and 1912. He is recognized as a pioneer in the development of special effects, trick photography, and newsreels. Le grand Méliès: In 1928, elderly Georges Méliès was found working at a toy stand in a Paris train station, his fame and fortune having deserted him. This documentary retraces his career through interviews with his friends, family, and colleagues. Quinze films de Georges Méliès is a collection of 15 of his best known fantasy films.
[Disc 1]. Magie Méliès / un film de Jacques Mény -- Śeance Méliès -- ##[Disc 2]. Grand Méliès / un film de Georges Franju.
Soundtracks in French or English. Le grand Méliès and Quinze films de Georges Méliès in French.
film
Keywords: Méliès, Georges; Mény, Jacques; Franju, Georges